Ethno-Cultural Values in Civil Education of Pupils in Poland - Iryna Kierzkowska (Pedagogical Discourse, 2012)
The problem of ethnic and cultural values ​​in the process of civic education of young people is extremely urgent. The main factor determining its relevance is the trend towards globalization of the modern world, one of the processes of which is human interstate migration. Every society, every human being has its place in time and space, in which it transforms the external and its own inner world. As a result of human migration processes, not only the social and cultural location of the person changes, but also the inner world of man, his identity. The intensification of social relations in recent years has spread to a global scale, through which, according to Anthony Giddens, regional phenomena, which are actually in a real geographical distance, are linked and have their counterparts in every part of the globe, and the process of globalization is becoming more national. . This trend is closely linked to the formation of a new phenomenon in public relations, namely transnationality, which is transcultural, though more limited than globalization, in nature. And as much as global processes are not dependent on specific national territories, so transnationality is always contained in the national context and is not overcome.